Evaluasi Potensi Batuan Induk pada Serpih di Formasi Talang Akar, Cekungan Sumatera Selatan dengan Metode Geokimia dan Petrografi Organik - , WINDA NOVIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
South Sumatera Basin is one of petroleum producing basins in Indonesia with Talang Akar Formation as source rock. In this research, analysis was conducted on fifteen outcrop samples of shale of Talang Akar Formation, where the sampling area is divided into two different areas, Pangkalan Balai and Lahat. Method used of this research are Rock Eval Pyrolysis and petrographic organic in order to determine the quality of source rock, the quantity of organic material, thermal maturity level and the relationship between geochemical parameters with organic petrography characteristics. The results of the analysis shows that the shale samples from Pangkalan Balai are quite potential to good potential as a source rock, classified as type II kerogen and containing maceral liptinit as dominant maceral. Its maturation level is immature. Whereas Lahat geochemistry data shows less potential to good potential to be source rock, classified as type I kerogen and maceral liptinit as the dominant constituent maceral. Its level of maturity is immature to early mature. The relationship between geochemical parameters with organic petrography characteristics, such as Tmax vs Ro, Ro vs. PI , S1 + S2 vs Ro and Ro vs. HI shows a positive correlation.